Electric and conventional vehicle usage in private and car sharing fleets in Germany. (April 2021) - Habla, Wolfgang; Huwe, Vera; Kesternich, Martin
Highlights: We provide empirical evidence on usage of conventional and electric vehicles. Electric vehicles are driven fewer kilometres than their conventional counterparts. This holds both for private and shared vehicles. Non-monetary barriers play a huge role for electric vehicle use and adoption. Car sharing intensifies usage of conventional cars but not of electric vehicles. Abstract: We use car-level micro data to provide empirical evidence on the usage of conventional and electric vehicles (EVs) in private and car sharing fleets in Germany. We shed light on both monetary and non-monetary barriers to EV usage by exploiting the feature that variable costs are identical for shared vehicles but different for private car owners across engine types. While drivers respond to monetary incentives when using conventional cars, this does not hold for EVs. We find that EVs are, on average, driven shorter distances than conventional vehicles, both in terms of annual and single-day mileage, even if costs are identical. We also document that car sharing intensifies the usage of conventional cars but not that of EVs.